Efficacy and safety of riociguat replacing PDE-5is for patients with pulmonary arterial hypertension: A systematic review and meta-analysis - Liu, Yu-Yang; Qu, Yi-Yang; Wang, Shang; Luo, Ci-Jun; Qiu, Hong-Ling; Li, Hui-Ting; Yuan, Ping; Wang, Lan; Li, Jin-Ling; Jiang, Rong; Zhang, Rui (Frontiers in Pharmacology, 2023)
Background Pulmonary arterial hypertension (PAH) is a rare and progressive disease. Some patients treated with phosphodiesterase type 5 inhibitors (PDE-5is) fail to reach treatment goals. As a novel soluble guanylate cyclase agonist, riociguat acts on the same pathway as PDE-5is but functions via different mechanisms. Whether riociguat is more effective and safer than PDE-5is is ambiguous. We aimed to evaluate the efficacy and safety of switching from PDE-5is to riociguat among these patients. Methods Original published articles were retrieved from PubMed/Medline, Embase, Web of Science, Open Grey and Google Scholar. Studies that assessed the World Health Organization functional class (WHO-FC), six-minute walking distance (6MWD), pulmonary vascular resistance (PVR), mean pulmonary arterial pressure (mPAP), cardiac index (CI) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) were collected. Adverse events after switching were evaluated. Results Ten published studies were included. Compared to PDE-5is, riociguat significantly increased the 6MWD by 26.45 m (weight mean difference (WMD) = 26.45 m, 95% confidence intervals (CI): 9.70-43.2 m, P = 0.002) and improved mPAP (WMD = -3.53 mmHg, 95% CI: -5.62-1.44 mmHg, P = 0.0009), PVR (WMD = -130.24 dyn·s·cm-5, 95% CI -187.43-73.05, P < 0.0001), CI (WMD = 0.36 L/min·cm-2, 95% CI: 0.25-0.47, P < 0.00001) and WHO-FC (OR = 0.11, 95% CI: 0.08-0.16, P < 0.0001) but not NT-proBNP. In addition, we did not observe the most common side effects during the replacement of riociguat for PDE-5is. Conclusions PAH patients benefit from PDE-5is compared to riociguat, including in hemodynamic parameters, 6MWD, WHO-FC and biomarkers.